Numerical analysis and optimization of crashworthiness of bionic hierarchical thin-walled square tubes - XU Fei; QIN RuiXian; CHEN BingZhi (Jixie qiangdu)
In order to improve the energy absorption efficiency of the conventional thin-walled square tube, a bionic hierarchical thin-walled square tube (BHST) was proposed by the microscopic trabecular structure of beetle wing sheaths. Based on the super folding element theory, a theoretical model of the mean crushing force of the bionic hierarchical thin-walled square tube was established. The axial energy absorption characteristics of the bionic hierarchical thin-walled square tube and the conventional multi-cell thin-walled square tube were analyzed by the nonlinear finite element method, and the influence of structural parameters on the crashworthiness of BHST4-2 structure was studied. The results show that the theoretical predictions match with the numerical simulation results, and the relative errors are all within 7%. The bionic hierarchical thin-walled square tube exhibits excellent crashworthiness. The wall thickness has a more significant effect on the crashworthiness of BHST4-2structure than the second-order square tube edge length. The radial basis function (RBF) model and the genetic algorithm were used for the multi-objective optimization of the BHST4-2 structure, and optimal al parameters of the structure were obtained. The results of the study provide new ideas for the design of thin-walled square tubes with excellent energy absorption properties.